2012
DOI: 10.5713/ajas.2011.11131
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Rain Tree Pod Meal Supplementation on Rice Straw Based Diets Using In vitro Gas Fermentation Technique

Abstract: The objective of this study was to determine the roughage to concentrate (R:C) ratio with rain tree pod meal (RPM) supplementation on in vitro fermentation using gas production technique. The experiment design was a 6×4 factorial arrangement in a CRD. Factor A was 6 levels of R:C ratio (100:0, 80:20, 60:40, 40:60, 20:80 and 0:100) and factor B was 4 levels of RPM (0, 4, 8 and 12 mg). It was found that gas kinetic, extent rate (c) was linearly increased (p<0.01) with an increasing level of concentrate while cum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
39
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 41 publications
12
39
0
1
Order By: Relevance
“…The above results suggested that condensed tannins from rambutan peel have a weaker inhibition effect on the fermentation rate. These results were in agreement with Anantasook and Wanapat (2012), who reported that supplementation of rain tree pod meal containing condensed tannins and saponins at 4, 8 and 12 mg/0.2 g DM had no effect on cumulative gas production. In contrast, Paengkoum et al (2015) reported that cumulative gas production was decreased by supplementation of mangosteen peel condensed tannins at 2-6% DM.…”
Section: Gas Kinetics Cumulative Gas Production and In Vitro Digestisupporting
confidence: 93%
“…The above results suggested that condensed tannins from rambutan peel have a weaker inhibition effect on the fermentation rate. These results were in agreement with Anantasook and Wanapat (2012), who reported that supplementation of rain tree pod meal containing condensed tannins and saponins at 4, 8 and 12 mg/0.2 g DM had no effect on cumulative gas production. In contrast, Paengkoum et al (2015) reported that cumulative gas production was decreased by supplementation of mangosteen peel condensed tannins at 2-6% DM.…”
Section: Gas Kinetics Cumulative Gas Production and In Vitro Digestisupporting
confidence: 93%
“…The average NH 3 -N concentration of all treatments was 14.21 mL dL -1 and was within the optimum ruminal NH 3 -N range of 12 and 17 mL dL -1 for optimal fermentation and rumen microbial growth (Anantasook and Wanapat, 2012;Lunsin et al, 2012). As expected, MPES and MPES + ES supplements increased the dietary levels of carbohydrate and nitrogen, resulting in an increase in NH 3 -N concentration levels and decrease in CO 2 production due to the microbial mass formation.…”
Section: Discussionsupporting
confidence: 65%
“…In the current study, the pH ranged from 6.94 to 7.19. These values are considered optimal for the normal rumen fermentation, for the synthesis of volatile fatty acid, and microbial protein (Wanapat and Pimpa, 1999;Anantasook et al, 2012), and are also within the range of 6.2 to 7.2, considered appropriate for optimal microbial activity (Van Soest, 1994), as expected for diets based on forage.…”
Section: Discussionmentioning
confidence: 99%
“…Rain tree pod meal, which contains condensed tannins and saponins, has the potential to manipulate rumen fermentation by depressing protozoa and methanogens thereby reducing methane production in in vitro (Anantasook and Wanapat, 2012). …”
Section: Introductionmentioning
confidence: 99%